2015
DOI: 10.1038/ismej.2015.131
|View full text |Cite
|
Sign up to set email alerts
|

Experimental insights into the importance of aquatic bacterial community composition to the degradation of dissolved organic matter

Abstract: Bacteria play a central role in the cycling of carbon, yet our understanding of the relationship between the taxonomic composition and the degradation of dissolved organic matter (DOM) is still poor. In this experimental study, we were able to demonstrate a direct link between community composition and ecosystem functioning in that differently structured aquatic bacterial communities differed in their degradation of terrestrially derived DOM. Although the same amount of carbon was processed, both the temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
303
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(314 citation statements)
references
References 54 publications
11
303
0
Order By: Relevance
“…In addition, many sequenced phylotypes, such as Nitrospira sp, Stenotrophomonas sp and Methylobac-5 terium sp have been associated with degradation capabilities (Cycoń et al, 2017;Daims et al, 2001;Wang et al, 2015). In short, the MAR microbial ecosystem studied in this work presents many more phylotypes than previous studies reported in groundwater systems (Logue et al, 2015), and thus, MAR can be considered an efficient remediation system.…”
Section: Matching Groundwater Model Ecological Disturbance Principlementioning
confidence: 71%
“…In addition, many sequenced phylotypes, such as Nitrospira sp, Stenotrophomonas sp and Methylobac-5 terium sp have been associated with degradation capabilities (Cycoń et al, 2017;Daims et al, 2001;Wang et al, 2015). In short, the MAR microbial ecosystem studied in this work presents many more phylotypes than previous studies reported in groundwater systems (Logue et al, 2015), and thus, MAR can be considered an efficient remediation system.…”
Section: Matching Groundwater Model Ecological Disturbance Principlementioning
confidence: 71%
“…S3), indicated that soil extract additions selected for copiotrophic bacteria, rare under oligotrophic conditions, but preponderant during periods of high allochthonous loadings. This agrees with previous observations from field (Crump et al ., 2003; Roiha et al ., 2011) and laboratory experiments (Logue et al ., 2016) showing that rapid shifts in community composition take place upon soil organic matter input. The loss and prevalence of the taxa determined in our study may be explained by their different functional adaptability, including differences in resource affinities (Cottrell & Kirchman, 2000; Salcher et al ., 2011; Heinrich et al ., 2013), physiological characteristics (Hahn & Pöckl, 2005; Šimek et al ., 2006) and genetic composition (Bauer et al ., 2006; Gómez‐Pereira et al ., 2012; Teeling et al ., 2012; Tveit et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The loss and prevalence of the taxa determined in our study may be explained by their different functional adaptability, including differences in resource affinities (Cottrell & Kirchman, 2000; Salcher et al ., 2011; Heinrich et al ., 2013), physiological characteristics (Hahn & Pöckl, 2005; Šimek et al ., 2006) and genetic composition (Bauer et al ., 2006; Gómez‐Pereira et al ., 2012; Teeling et al ., 2012; Tveit et al ., 2013). Further, changes in lake bacterial community composition have been attributed not only to the differential response of individual bacterial taxa to DOM inputs, but also to the introduction of soil bacteria with allochthonous sources or to incubation effects (Crump et al ., 2003; Logue et al ., 2016). In our experiments, however, the addition of soil‐borne bacteria with the soil extracts was not confirmed when using staining techniques and microscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These groups are considered to be opportunistic bacteria in surface waters, and they responded rapidly to the enrichment derived from copepod excretion. Several studies have suggested that enrichment experiments tend to enhance the abundance of microorganisms rarely found in nature, but that have opportunistic and copiotrophic qualities that allow them to rapidly adapt to changes in environmental conditions, outcompeting abundant groups in the field (Nelson and Wear, 2014;Pedler et al, 2014;Logue et al, 2016). Lauro et al (2009) argued that copiotroph bacteria have a higher genetic potential to sense and rapidly respond to a sudden nutrient influx, compared to the more widely distributed oligotrophic bacteria.…”
Section: Bacterial Response To the Copepod Excretion Productsmentioning
confidence: 99%